The Influence of the Use of Fintech on the Development of Literacy and Financial Inclusion Among MSMEs in Kupang City - Maria Virayati Kofi; Novi Theresia Kiak; Cicilia A. Tungga (Formosa Journal of Sustainable Research, 2023)
This study aims to explain the effect of fintech on financial literacy and inclusion in MSMEs in Kupang City.  This research is a quantitative research with primary data, namely by distributing questionnaires to MSMEs in Kupang City.  The data analysis technique used was path analysis using SPSS software version 29. Respondents in this study were 100 SMEs in Kupang City.  The results of this study indicate that fintech has a significant positive effect on financial literacy in MSMEs in Kupang City, fintech has a significant positive effect on financial inclusion in MSMEs in Kupang City, financial literacy has a significant positive effect on financial inclusion in MSMEs in Kupang City, fintech has a significant positive effect on  financial literacy through financial inclusion in MSMEs in Kupang City.  With these results, it is hoped that MSMEs need to increase the use of financial technology because it has been proven to increase financial literacy and inclusion